Bariatric Surgery Complications Leading to Small Bowel Transplant: A Report of 4 Cases. (May 2014) - Raheem, Sulieman Abdal; Deen, Omer J.; Corrigan, Mandy L.; Parekh, Neha; Quintini, Cristiano; Steiger, Ezra; Kirby, Donald F.
Obesity is a major chronic disease affecting the U.S. population. Bariatric surgery has consistently shown greater weight loss and improved outcomes compared with conservative therapy. However, complications after bariatric surgery can be catastrophic, resulting in short bowel syndrome with a potential risk of intestinal failure, ultimately resulting in the need for a small bowel transplant. A total of 6 patients became dependent on home parenteral nutrition (HPN) after undergoing bariatric surgery at an outside facility. Four of the 6 patients required evaluation for small bowel transplant; 2 of the 6 patients were successfully managed with parenteral nutrition and did not require further small bowel transplant evaluation. Catheter-related bloodstream infection, a serious complication of HPN, occurred in 3 patients despite extensive patient education on catheter care and use of ethanol lock. Two patients underwent successful small bowel transplantation, 1 died before transplant could be performed, and 1 was listed for a multivisceral transplantation. Surgical procedures to treat morbid obesity are common and growing in popularity but are not without risk of serious complications, including intestinal failure and HPN dependency. Despite methods to prevent complications, failure of HPN may lead to the need for transplant evaluation. In selected cases, the best therapeutic treatment may be a small bowel transplant to resolve irreversible, post–bariatric surgery intestinal failure.